Mucinous Adenocarcinoma of the Anal Canal: clinical case and how to avoid errors in its diagnosis - Trostchansky, Ivan; Pontillo, Marcelo; González, Catalina; Zeoli, Mariana; Valiñas, Roberto (Cirugía del Uruguay, 2023)
The mesorectal surgery and the neoadyuvant treatment have changed the management of rectal adenocarcinoma. The Nigro protocol had the same impact on the squamous cell cancer of the anus. However, the adenocarcinoma of the anus is an infrequent pathology, related to chronic inflammatory processes such as perianal fistulas and its treatment generates controversy. The lack of knowledge about clinical and imaging characteristics of this pathology can lead to diagnostic confusion, mainly with a perianal abscess. We hereby present the clinical case of an anal canal adenocarcinoma in relation to a chronic perianal fistula and a review of the current literature on the subject.